Strategi pengembangan ekonomi regional dengan pendekatan sectoral economic analysis di provinsi kepulauan Riau : Regional economic development strategy with a sectoral economic analysis approach in the Riau Islands Province - Siti Ahyuni; Siti Lailatul Latipah; Nasarudin (Economic Military and Geographically Business Review, 2023)
The Riau Islands Province is a self-governing strategic region with abundant natural resources in agriculture, maritime, and industry, resulting in higher per capita income than other provinces. According to the Central Statistics Agency (BPS), Riau has abundant natural resources. However, it is still classified as a country with the highest unemployment rate, ranking third after Java with 8.52%. As a result, Riau's GRDP level is still in the middle-income category, where groups have income levels between the low and high-income categories. This research uses a sectoral approach to analyze and determine regional development steps according to critical sectors in Riau with the Analytical Hierarchical Process (AHP) methodology. It focuses on local activity areas. The research method applied is a sector analysis approach, which includes LQ and DLQ analysis, shift share, and class typology. Based on research from Economic Growth, Riau has nine potential economic sectors: agriculture, manufacturing, hotels and restaurants, construction, transportation, telecommunications, mining, financial services, business services, and real estate. These sectors provide the basis for formulating government policies that will absorb labor and wage levels to narrow unemployment and then increase the regional Gross Domestic Product (GRDP), which Riau can hope will increase.